2020
DOI: 10.18632/aging.102673
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of lncRNA XIST inhibits non-small cell lung cancer growth and promotes chemosensitivity to cisplatin

Abstract: Long noncoding RNAs (lncRNAs) play critical roles in tumour progression and metastasis. Emerging evidence indicates that the lncRNA X inactive-specific transcript (XIST) is dysregulated in several tumor types, including non-small cell lung cancer (NSCLC). However, in NSCLC and other cancers the oncogenic mechanism of XIST remains incompletely understood. Here, we confirmed that XIST is upregulated in human NSCLC specimens, and is especially overexpressed in tumors previously treated with cisplatin (cis-diammin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“… 27 LncRNAs, HAS2-AS1 and XIST, accelerate resistance to chemotherapy in NSCLC. 28 , 29 In this study, we found that LINC01089 overexpression inhibited the proliferation, migration, and invasion of A549 and SK-MES-1, suggesting that LINC01089 acts as an anti-oncogene to inhibit tumorigenesis and metastasis in NSCLC. A previous study found that LINC01089 inhibits cell invasion in vitro and tumor metastasis in vivo and acts as a tumor suppressor gene and prognostic biomarker in breast cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 61%
“… 27 LncRNAs, HAS2-AS1 and XIST, accelerate resistance to chemotherapy in NSCLC. 28 , 29 In this study, we found that LINC01089 overexpression inhibited the proliferation, migration, and invasion of A549 and SK-MES-1, suggesting that LINC01089 acts as an anti-oncogene to inhibit tumorigenesis and metastasis in NSCLC. A previous study found that LINC01089 inhibits cell invasion in vitro and tumor metastasis in vivo and acts as a tumor suppressor gene and prognostic biomarker in breast cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 61%
“…In another research, downregulation of LncRNA-XIST was demonstrated to relieve its suppression of Smad2 nuclear translocation, subsequently triggering transcriptional activation of P53 and NLRP3. Therefore, the relationship between XIST and pyroptosis was verified from multiple perspectives (61). In addition to NLRP3/caspase-1/ GSDMD pathway, the induction of GSDME cleavage in NSCLC causes pyroptosis and inhibits proliferation as well.…”
Section: Lung Cancermentioning
confidence: 96%
“…Emerging evidence has shown that DDP could induce pyroptotic cell death in various cells 9 , 29 . Enhancing the pyroptotic effect can increase the chemosensitivity to DDP in several cancer cells, including esophageal cancer cells 30 , oesophageal squamous cell carcinoma cells 31 , gastric cancer cells 29 , and non-small cell lung cancer cells 32 . Nevertheless, it is still unclear whether DDP induces TNBC cell pyroptosis.…”
Section: Discussionmentioning
confidence: 99%